Role of staging laparoscopy in upstaging CT findings and influencing treatment decisions in gastric cancers - Indrakumar, Abhinay; Mandakulutur, Ganesh S.; Banavara, Keerthi R. (International Journal of Research in Medical Sciences, 2016)
Background: It is estimated that 990000 new gastric cancer (GC) cases occur in the world annually. The aim of this study was to examine the accuracy of laparoscopy in staging patients with gastric cancer in comparison with preoperative computed tomography (CT) examination and to determine the influence of staging laparoscopy on treatment decisions in gastric cancers. Methods: This was a prospective study conducted in a tertiary care hospital between August 2014 and February 2016. Thirty patients out of a series of 60 patients with gastric adenocarcinoma underwent a preoperative staging CT followed by a staging laparoscopy. The strengths of the agreement between the CT stage, the laparoscopic stage, and the final histopathological stage were determined by the weighted Kappa statistic (Kw). The number of patients with treatment decision-changes was counted. Results: The strengths of agreement between the CT stage and the final histopathological stage were Kw- 0.314 (95% confidence interval [CI]; 0.03-0.66; P≥0.0001) for T stage and 0.00 (95% CI; 0.0-0.00) for M stage, compared with 0.668 (95% CI; 0.39-0.98; P≥0.0001) and 1.00 (95% CI; 1.0-1.0; P≥0.0001) for the laparoscopic T and M stages, respectively. Unsuspected metastases that were not detected by CT, were found in 12 patients at laparoscopy, all of whom had T3 or T4 locally advanced tumors evident on CT. Conclusions: Preoperative laparoscopic staging of gastric cancer is indicated for potential surgical candidates with locally advanced disease in the absence of metastases on CT and influences treatment decision making apart from preventing unnecessary laparotomies.